2018
DOI: 10.20944/preprints201802.0051.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applications of Metals for Bone Regeneration

Abstract: The regeneration of bone tissue is a main purpose of most therapies in dental medicine. For bone regeneration, calcium phosphate (CaP)-based substitute materials based on natural (allo- and xenografts) and synthetic origins (alloplastic materials) are applied for guiding the regeneration processes. The optimal bone substitute has to act as a substrate for bone ingrowth into a defect, while it should be resorbed even in the time frame needed for complete regeneration up to the condition of restitution ad integr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 219 publications
(266 reference statements)
0
27
0
Order By: Relevance
“…Our study revealed that new bone was bound to Ti6Al4V-6.5wt%Cu alloy more tightly than to Ti6Al4V alloy, indicating that Ti6Al4V-6.5wt%Cu alloy has better biocompatibility. Studies have shown that copper ions significantly promote osteogenic differentiation of hBMSCs by improving expression of bone-related genes like alkaline phosphatase (ALP), osteopontin (OPN), and osteocalcin (OCN) [ [26] , [27] , [28] ]. Our immunohistochemical staining showed that the expression of osteogenic proteins in bone tissue around the infected bone defects filled with Ti6Al4V-6.5wt%Cu alloy was significantly higher than that filled with Ti6Al4V alloy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that new bone was bound to Ti6Al4V-6.5wt%Cu alloy more tightly than to Ti6Al4V alloy, indicating that Ti6Al4V-6.5wt%Cu alloy has better biocompatibility. Studies have shown that copper ions significantly promote osteogenic differentiation of hBMSCs by improving expression of bone-related genes like alkaline phosphatase (ALP), osteopontin (OPN), and osteocalcin (OCN) [ [26] , [27] , [28] ]. Our immunohistochemical staining showed that the expression of osteogenic proteins in bone tissue around the infected bone defects filled with Ti6Al4V-6.5wt%Cu alloy was significantly higher than that filled with Ti6Al4V alloy.…”
Section: Discussionmentioning
confidence: 99%
“…68 The release of metallic ions could also be beneficial for the regeneration of bone as many metallic ions are important for the proper function of the body. 69…”
Section: Biomaterialsmentioning
confidence: 99%
“…Both options can result in complications such as allergic reactions or secondary fractures [ 67 , 68 ]. Another approach uses the functional role of metal ions in the physiological and cellular environment to induce cell proliferation or osteogenic differentiation [ 54 ]. Based on the suggested approach, D’Mello et al [ 55 ] observed bone healing of calvarial defects in rats using copper-loaded chitosan scaffolds.…”
Section: Bone Graft Substitutes For the Reconstruction Of Large Bomentioning
confidence: 99%
“…Recent research has focused more on the creation of biodegradable materials such as magnesium alloys, ceramics and polymers. Improvements have been achieved by modifying the materials, for example with nanoparticles to increase antibiotic effects [ 70 , 71 , 72 ] or cell functionality [ 73 , 121 , 194 ], with metal ions to take advantage of their functional role in the physiological and cellular environment [ 54 , 55 , 56 ] or with proteins or RNAs to induce osteosynthesis [ 16 , 17 , 18 , 19 , 20 ]. The use of magnesium alloys shows promising potential as a bone graft substitute [ 65 , 195 ], not only because of its mechanical properties but also because of its physiological ability to induce the migration of osteoblasts to the implantation site as they migrate to environments of high Mg ion concentrations [ 56 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation